Analisis Strategi Komunikasi Pemasaran pada Akun Instagram Agen Perjalanan Wisata @doctrip.id - Aulia, Muhammad Rizki; Hasanah, Kiki; Lestiohadi, Lestiohadi (Digital Business Progress, 2025)
This study analyzes the marketing communication strategy on the Instagram account of the travel agency Doctor Trip Indonesia @doctrip.id using a descriptive qualitative approach with content analysis method. Based on an examination of the 50 most recent posts (September–November 2025), the strategy focuses on three main elements: captivating visuals, interaction and collaboration and Call to Action (CTA). The results show increased engagement, customer trust and follower growth (140,675 as of November 2025). This research aims to provide recommendations for other travel companies to optimize Instagram as an authentic and interactive digital marketing channel.